Analisis Koreksi Fiskal Atas Pendapatan dan Biaya Dalam Menentukan Pajak Penghasilan Badan Terutang Pada CV Dirgantara Jaya - Murdan Sianturi; Anisa Hildayanti (Mulia Pratama, 2022)
The object of this research is CV Dirgantara Jaya. The purpose of this study was to determine the magnitude of the fiscal correction on income to the corporate income tax payable on CV Dirgantara Jaya, determines the amount of fiscal correction on expenses for the corporate income tax payable to CV Dirgantara Jaya, and determine the magnitude of the fiscal correction on income and expenses for the corporate income tax payable to CV Dirgantara Jaya. The type of research data used in this study is quantitative research which is expressed in the form of numbers, values or amounts in the form of financial statements, namely the balance sheet and income statement for 2021 and 2022 on CV Dirgantara Jaya, the source of data used in this study is secondary data, in this study researchers took the form of financial reports taken directly from the company. As for the population in this study is the financial statements (commercial) CV Dirgantara Jaya. And the samples in this study are the financial reports (profit and loss and balance sheet), components of costs and income for 2021 and 2022 on CV Dirgantara Jaya. In this study the authors also used data collection methods by way of library research and field research. The author's data analysis method uses quantitative analysis and descriptive analysis. The results of this study concluded that there are differences between corporate income tax payable by company and the researcher's analysis. The amount of corporate income tax owed by a company can be determined by reconciling commercial profit and loss to a taxable income statement. After carrying out a fiscal reconciliation, the author obtains a fiscal correction on income against corporate income tax payable in 2021 of IDR 169,328,000 and a fiscal correction on income against corporate income tax payable in 2022 of IDR 150,870,431. There is a fiscal correction of costs for corporate income tax payable in 2021 of IDR 10,790,500 and a fiscal correction for costs for corporate income tax payable for 2022 of IDR 17,615,750. Then the total fiscal correction on income and expenses for the corporate income tax payable in 2021 is IDR 180,118,500 and the fiscal correction for income and expenses for the corporate income tax payable for 2022 is IDR 168,486,181